THE INFLUENCE OF COMPANY CONNECTION, POLITICAL LEVERAGE AND SIZE RELATIONS ON TAX AVOIDANCE (In AgriculturallSector Companies Listedlon the Indonesia Stock Exchange for the 2016-2018 Period) - Tiberias, Eodia; Hutadjulu, Fharel; Florencia, Carolina (Universitas Kristen Indonesia, 2021)
Tax revenue playsIan important role in running the government becauseiit provides the largesticontributionito state revenue. Companies often take steps to reduce their tax burden. One of the actions taken is tax evasion. This research was conducted to analyze theieffect of politicaliconnection, leverage and company size on tax avoidance. The population in this study were agricultural sector companiesilisted on the Indonesia Stock Exchange in 2016-2018. Data obtained from published annual financial reports. The sampling technique was purposive sampling method which resulted in 57 samples from 19 companies for 3 years of observation in 2016-2018. The researchidata was collected by means of observational study and literature study methods. Theianalytical method used is multiple linear regression analysis. The results in this study indicate that Political Connection has a significant negative effect on Tax Avoidance, Leverage has no significant effect on Tax Avoidance and Company size has a significant effection Tax Avoidance. Keywords: Political Connections, Leverage, Size, Tax Avoidance